1996
DOI: 10.1016/s0035-9203(96)90537-4
|View full text |Cite
|
Sign up to set email alerts
|

Blood, bone marrow and splenic lymphocyte subset profiles in Indian visceral leishmaniasis

Abstract: We examined the lymphocyte subsets in peripheral blood, bone marrow and spleen of 11 patients with acute visceral leishmaniasis (VL) and 9 with chronic VL before and after 8 weeks of antileishmanial therapy. On admission, the CD4 cell count was depressed in the peripheral blood of acute and chronic VL cases as compared to the value in 10 normal control subjects. In contrast, CD4 cell counts were higher in the bone marrow in acute and chronic cases, and in splenic aspirates of chronic cases only, compared to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…The study by Rohatgi et al 16 in leishmaniasis patients found that the pretreatment CD4 cell count was depressed in the peripheral blood of acute and chronic VL cases but higher in the bone marrow. An influx of CD4 cells to the bone marrow and spleen might account for the fall in the CD4:CD8 cell ratio in the blood observed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The study by Rohatgi et al 16 in leishmaniasis patients found that the pretreatment CD4 cell count was depressed in the peripheral blood of acute and chronic VL cases but higher in the bone marrow. An influx of CD4 cells to the bone marrow and spleen might account for the fall in the CD4:CD8 cell ratio in the blood observed.…”
Section: Discussionmentioning
confidence: 96%
“…An influx of CD4 cells to the bone marrow and spleen might account for the fall in the CD4:CD8 cell ratio in the blood observed. 16 Studies using experimental models of malaria in immune-deficient mice and chickens have shown that resistance to blood-stage infection is mediated by protective antibodies and T celldependent cell-mediated mechanisms of immunity. 17 Therefore, it seems that leishmaniasis-mediated CD4 lymphopenia may have nullified the protective effect against malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Many human diseases, such as leishmaniasis and tuberculosis, are associated with reduced cholesterol level ( 13,50 ) coupled with immunosuppression ( 14,51 ). It was observed that under certain pathological conditions, like leishmaniasis, there is an expansion of CD8 + T cells coupled with a decline of CD4 + T cells ( 52,53 ). It has been shown that statins, cholesterol lowering drugs, reduce IFN-␥ -inducible expression of MHC II, but do not reduce constitutive expression of MHC II in professional APCs ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that m ␤ -M ⌽ s and m ␤ -M ⌽ -CL-AN showed compromised ability to stimulate T cell hybridoma (HyH12.6, A k restricted) as evident from the 80% decrease in IL-2 production as compared with N-M ⌽ s in presence of HEL [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] peptide, whereas m ␤ -M ⌽ -CL showed normal T cell stimulating ability ( Fig. 1C ).…”
Section: T Cell Stimulation Depends On Membrane Cholesterol But Not Omentioning
confidence: 99%
“…Previously, we showed that the assembly of IFN-gR subunits R1 and R2 is disturbed under parasitized conditions; IFN-g binds to the receptor but is unable to transduce the signal to kill intracellular L. donovani parasites (14). It was reported that the numbers of CD4 + T cells decreased, whereas CD8 + T cells increased, in the PBMCs in acute visceral leishmaniasis (15). It was shown that L. donovaniinfected granuloma-derived Kupffer cells present endogenous leishmanial Ag to CD8 + T cells (16).…”
mentioning
confidence: 99%